The producer's business handbook the roadmap for the balanced film producer - Lee, John J.; Gillen, Anne Marie (Routledge, 2018)
"Gain a comprehensive understanding of the business of global entertainment and learn to successfully engage in all aspects of global production with the revised and updated Producer's Business Handbook. Learn how to cultivate relationships with key industry players including your home and international territory studios, agencies, attorneys, talent, completion guarantors, banks, and private investors. This new fourth edition includes the latest opportunities presented by changing technology and their impact on the producer's ability to finance, globally release, brand, and monetize content. Also included is information on how producers can now more beneficially connect with their audiences, project earnings, distribution methods, and funding, in addition to coverage on new opportunities created by the explosive growth of VR, AR, 360, gaming, and the rapid conversion to OTT.Additional features include:Updated production financing worksheets '" an essential tool for producers;Expanded information for low-budget independent producers, internationally-based producers, producers using government funding, and film school students alike;Coverage of China's changing entertainment landscape, their entertainment consumption, commitment to produce content for the big global territories, and more;New, full-color illustrations and symbols, visually simplifying complex topics."--Provided by publisher.
Includes index. - Description based on print version record and CIP data provided by publisher
Keywords: Motion picture industry -- Handbooks, manuals, etc -- Finance -- United States; Motion pictures -- Handbooks, manuals, etc -- Marketing -- United States; Motion pictures -- Handbooks, manuals, etc -- Production and direction; Cinéma; Production et réalisation; Guides, manuels, etc; Cinéma; Industrie; États-Unis; Finances; Guides, manuels, etc; Motion picture industry; Finance; Motion pictures; Marketing; Motion pictures; Production and direction; United States; Handbooks and manuals